STRATEGI PENINGKATAN EFISIENSI BIAYA PADA NILAI LEMBAGA KEUANGAN SYARIAH BERBASIS STOCHASTIC FRONTIER APPROACH (SFA) DAN DATA ENVELOPMENT ANALYSIS(DEA) - Umi Hoeroh; Nur Diana (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe purpose of this study was to determine the strategy of increasing cost efficiency in value-basedIslamic financial institutions Stochastic Frontier Approach (SFA) and Data Envelopment Analysis(DEA). To determine the effect on the performance efficiency prifitabilitas Islamic Financial Institutions.This research was conducted against five Islamic Financial Institutions with the largest total assets in July2016 period, ie that bank Muamalat Indonesia, Islamic Bank Mandiri, Bank Mega Syariah BRI Syariah,and Bank Bukopin. Financial Statement Data that has been published by Bank Indonesia (BI) and listedon the Indonesia Stock Exchange (BEI). The period of observation in this study is from 2013 to 2015.This research uses Correlational research, operational research variables using Third Party Funddata, Personnel expense or burden of Labor, Total Assets and Total Funding with each scale ratio. Datacollection method is documentation while data analysis using the calculation of the efficiency of LKS(Islamic Financial Institutions) in terms of the cost by using the method of approach to cost efficiency,while for the calculation using a parametric approach Stochastic Frontier Approach (SFA) and nonparametric Data Envelopment Analysis (DEA) to R-Studio program. And to measure the impact onoutput and output variables on the efficiency of researchers used multiple linear regression analysis usingSPSS.The results showed that the overall average, both the SFA and DEA methods, LKS fifth condition isefficient. The average value of efficiency LKS SFA and DEA methods 1.000% and 0.99212%. Of the twomethods, LKS has the highest level of efficiency is Bank Syariah Bukopin and the lowest is the BankMega Syariah. The results of multiple linear regression analysis of the effect of input variables on outputshows that the Third Party Funds, expenses or expenses Personnel Labor, Total Assets Total Financingpositive influence on worksheets. There is influence between the input and output components of thelevel of cost efficiency Islamic Financial Institutions is heavily influenced by the Operating Expenses.This means that the higher the Operating Expenses Total Funding will increase and conversely the lowerthe Operating Expenses Total Funding will decrease.Keywords: Financial Statements, Islamic Financial Institutions, Efficiency, Stochastic FrontierApproach (SFA) and Data Envelopment Analysis (DEA)